2008
DOI: 10.1007/s00464-008-0030-x
|View full text |Cite
|
Sign up to set email alerts
|

Two-center experience in the treatment of hemorrhoidal disease using Doppler-guided hemorrhoidal artery ligation: functional results after 1-year follow-up

Abstract: Based on our results we may conclude that DGHAL is a safe and effective method and may offer an important alternative to operative hemorrhoidectomy with no risk of postoperative stool incontinence, minimal postoperative pain, and early return of patients to their normal activities. Nevertheless, this is a fairly new procedure with a short-term follow-up. Until 5-year observations of large, multicenter, randomized trials are published we cannot recommend this method as a gold-standard procedure, although it sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 20 publications
2
25
0
2
Order By: Relevance
“…Both groups were positive about the procedure, and no patient reported being dissatisfied. Similar to the findings of a number of studies reported in the literature [10,11,16,22], our results showed that DGHAL was associated with significantly less postoperative discomfort. Our DGHAL patients had a shorter delay before the first bowel movement, significantly lower degree of pain during defecation, shorter hospital stay, less analgesic intake, and quicker return to normal activities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both groups were positive about the procedure, and no patient reported being dissatisfied. Similar to the findings of a number of studies reported in the literature [10,11,16,22], our results showed that DGHAL was associated with significantly less postoperative discomfort. Our DGHAL patients had a shorter delay before the first bowel movement, significantly lower degree of pain during defecation, shorter hospital stay, less analgesic intake, and quicker return to normal activities.…”
Section: Discussionsupporting
confidence: 92%
“…Conventional surgical hemorrhoidectomy represents the most effective currently available treatment, but it may require hospitalization and is associated with severe postoperative pain lasting up to 3 weeks, which can affect the daily functioning of up to 75% of patients. Additionally, radical hemorrhoidal resection may be accompanied by various complications, such as sphincter dysfunction (up to 25% of patients) postoperative bleeding or infection (up to 5-15% of patients) and a high recurrence rate (up to 30%) [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…This method, comparable to the elastic band ligations performed blind for several decades, is effective in internal hemorrhoidal disease where there is no prolapse. Several descriptive studies [20][21][22][23][24][25] have reported a shortterm efficacy rate of 90 %, and long-term efficacy of 70-92 %. Post-operative pain was present in 1-6 % of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Sie kann jedoch einen Klinikaufenthalt erfordern und ist mit großen postoperativen, bis zu 3 Wochen andauernden Schmerzen assoziiert, was das Alltagsleben von bis zu 75% der Patienten beeinträchtigen kann. Darüber hinaus kann die radikale Hämorrhoidenresektion mit verschiedenen Komplikationen einhergehen, wie Sphinkterstörungen (bis zu 25% der Patienten), postoperativen Blutungen oder Infektionen (bis zu 5-15% der Patienten) und einer höheren Rezidivrate (bis zu 30%) [16,17,18]. Bei dieser Methode schneidet der Operateur nicht die Hämorrhoiden heraus, sondern eher einen kreisförmigen Zylinder von Mukosa und Submukosa 2-3 cm oberhalb der Linea dentata.…”
Section: Diskussionunclassified
“…Beide Gruppen sahen den Eingriff positiv und kein Patient berichtete, unzufrieden zu sein. Ähnlich den Ergebnissen einer Anzahl von in der Literatur berichteten Studien [10,11,16,22] zeigten unsere Ergebnisse, dass die DGHAL mit signifikant weniger postoperativen Beschwerden assoziiert war. Unsere DGHAL-Patienten hatten eine kürzere Zeit bis zur ersten Darmentleerung, ein signifikant niedrigeres Ausmaß von Schmerzen während der Defä-kation, einen kürzeren Klinikaufenthalt, geringeren Schmerzmittelverbrauch sowie eine schnellere Rückkehr zu normalen Aktivitäten.…”
Section: Diskussionunclassified